HSP40 proteins use class-specific regulation to drive HSP70 functional diversity - Faust, Ofrah; Abayev-Avraham, Meital; Wentink, Anne; Maurer, Michael; Nillegoda, Nadinath B.; London, Nir; Bukau, Bernd; Rosenzweig, Rina (Nature, 2020)
The ubiquitous heat shock protein 70 (HSP70) family consists of ATP-dependent molecular chaperones, which perform numerous cellular functions that affect almost all aspects of the protein life cycle from synthesis to degradation1-3. Achieving this broad spectrum of functions requires precise regulation of HSP70 activity. Proteins of the HSP40 family, also known as J-domain proteins (JDPs), have a key role in this process by preselecting substrates for transfer to their HSP70 partners and by stimulating the ATP hydrolysis of HSP70, leading to stable substrate binding3,4. In humans, JDPs constitute a large and diverse family with more than 40 different members2, which vary in their substrate selectivity and in the nature and number of their client-binding domains5. Here we show that JDPs can also differ fundamentally in their interactions with HSP70 chaperones. Using nuclear magnetic resonance spectroscopy6,7 we find that the major class B JDPs are regulated by an autoinhibitory mechanism that is not present in other classes. Although in all JDPs the interaction of the characteristic J-domain is responsible for the activation of HSP70, in DNAJB1 the HSP70-binding sites in this domain are intrinsically blocked by an adjacent glycine-phenylalanine rich region—an inhibition that can be released upon the interaction of a second site on DNAJB1 with the HSP70 C-terminal tail. This regulation, which controls substrate targeting to HSP70, is essential for the disaggregation of amyloid fibres by HSP70-DNAJB1, illustrating why no other class of JDPs can substitute for class B in this function. Moreover, this regulatory layer, which governs the functional specificities of JDP co-chaperones and their interactions with HSP70s, could be key to the wide range of cellular functions of HSP70.